1995
DOI: 10.1111/j.1469-7610.1995.tb02318.x
|View full text |Cite
|
Sign up to set email alerts
|

The Orphans of Eritrea: A Comparison Study

Abstract: The social-emotional state and cognitive development was compared between a group of 74 4-7-year-old Eritrean orphans and refugee children living in families. Both groups had been exposed to the chronic stresses of war and drought, and the orphans had, in addition, lost both parents to the violence of war, and were living in an overcrowded orphanage. Contrary to expectations, there were relatively few clinically significant differences between comparison groups. The orphans showed more behavioral symptoms of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
(7 reference statements)
0
40
0
Order By: Relevance
“…In addition, their interactions with adult strangers were observed under free field conditions. The comparison of orphans and refugee children has been described in detail in earlier reports (Wolff, Dawit, et al, 1995 ;Wolff, Tesfai, Eyasso, & Aradom, 1995), and only the main findings will be summarized here. -up Studies (1996) Subjects.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, their interactions with adult strangers were observed under free field conditions. The comparison of orphans and refugee children has been described in detail in earlier reports (Wolff, Dawit, et al, 1995 ;Wolff, Tesfai, Eyasso, & Aradom, 1995), and only the main findings will be summarized here. -up Studies (1996) Subjects.…”
Section: Methodsmentioning
confidence: 97%
“…Group comparisons indicated that the Solomuna orphans showed significantly more behavioral symptoms on the BSQ than refugee children ; sleep disturbances, eating disorders, and aggressive interactions with peers accounted for most of the group differences (Wolff, Tesfai, et al, 1995). The group differences in emotional state were illustrated more graphically by free field observations.…”
Section: Follow-up Studiesmentioning
confidence: 99%
“…The low average IQ of the orphans is perhaps due to the harsh circumstances that such children often encounter (but see Wolff, Tesfai, Egasso, & Aradom, 1995). Moreover, average IQ in rural areas is often lower than it is in urban areas (e.g., Loehlin, 2000).…”
Section: Coloured Progressive Matricesmentioning
confidence: 96%
“…The severities of the PTSD scores were positively correlated with a range of psychological difficulties. Wolff and Tesfai (1995). Using a prospective cohort design, this study examined social functioning, emotional functioning, and cognitive development in a sample of 148 children who were living with foster families or in orphanages.…”
Section: Resultsmentioning
confidence: 99%